2003
DOI: 10.1093/qjmed/hcg038
|View full text |Cite
|
Sign up to set email alerts
|

Sudden, unexpected cardiac or unexplained death in England: a national survey

Abstract: In 4.1% of sudden unexpected deaths under 65 years, no cause was found. Until it becomes accepted practice to identify these cases by a name, such as Sudden Adult Death Syndrome (SADS), it will not be possible to study their aetiology systematically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
2
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 21 publications
7
86
2
7
Order By: Relevance
“…On the other hand, it can of course take some time for rare, but serious chronic toxic effects that can cause sudden death, such as clozapine-induced cardiomyopathy or myocarditis (Wooltorton, 2002), to be associated with a given compound. This latter comment notwithstanding, it has been suggested that the aetiology of sudden, unexpected, cardiac-related or otherwise unexplained deaths will not be studied systematically until such deaths are identified by a name such as Sudden Adult Death Syndrome (SADS; Bowker et al, 2003). Figure 1).…”
Section: Post-mortem Toxicologymentioning
confidence: 99%
“…On the other hand, it can of course take some time for rare, but serious chronic toxic effects that can cause sudden death, such as clozapine-induced cardiomyopathy or myocarditis (Wooltorton, 2002), to be associated with a given compound. This latter comment notwithstanding, it has been suggested that the aetiology of sudden, unexpected, cardiac-related or otherwise unexplained deaths will not be studied systematically until such deaths are identified by a name such as Sudden Adult Death Syndrome (SADS; Bowker et al, 2003). Figure 1).…”
Section: Post-mortem Toxicologymentioning
confidence: 99%
“…[6][7][8][9][10] A differential diagnosis includes the entity known as idiopathic myocardial fibrosis (IMF), which accounts for 1-3% of cases of SCD. [11][12][13] IMF is characterised by heterogeneous interstitial fibrosis with a predilection for the inferior LV wall. 13 Replacement fibrosis is also observed and fatty infiltration is usually absent.…”
Section: Case Reportmentioning
confidence: 99%
“…43 A national survey of the US law enforcement agency reported that 81% of police officers respond to emergency and 50% provide some level of medical care. 5 Security Officers in Casinos The placement of AEDs in casinos has produced favorable outcomes; 44 over approximately 3 years, security officers in 10 casinos used AEDs in 148 cases of cardiac arrest. The mean time from witnessed collapse to delivery of the first shock by the security officer was considerably faster (4.4 min) than the paramedics (10 min).…”
Section: Types Of Responders and Work Places For The Pad Programmentioning
confidence: 99%